2021
DOI: 10.1167/iovs.62.9.41
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Microvascular Integrity Association With Anti-VEGF Treatment Response for Diabetic Macular Edema

Abstract: To investigate the association between foveal microvascular integrity and antivascular endothelial growth factor (VEGF) treatment response for diabetic macular edema (DME).METHODS. This retrospective study enrolled 58 eyes (from 45 patients) with DME. Treatment strategy was three to five monthly anti-VEGF injections followed by a PRN protocol. Treatment with an intravitreal corticosteroid would be considered for persistent DME after five consecutive anti-VEGF injections. Eyes achieving a treatment-free interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Studies have reported an assortment of treatment schedules prior to considering a subject to be with recalcitrant DME, including three consecutive monthly anti-VEGF treatments, 8 four successive anti-VEGF injections, 9 or a minimum of six consecutive anti-VEGF treatments. 10 However, a subset of patients with DME may need 6–12 months of continuous treatment in order to resolve the fluid on OCT 11 so the author only included patients in this study who had undergone at least eight aflibercept injections over 12 months to make sure the patient with DME was truly recalcitrant to aflibercept treatment. Recurring anti-VEGF treatments over long time periods may produce immunoreactivity and tachyphylaxis with reduced therapeutic effect, 12 and changing to another anti-VEGF medication may sometimes overcome this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported an assortment of treatment schedules prior to considering a subject to be with recalcitrant DME, including three consecutive monthly anti-VEGF treatments, 8 four successive anti-VEGF injections, 9 or a minimum of six consecutive anti-VEGF treatments. 10 However, a subset of patients with DME may need 6–12 months of continuous treatment in order to resolve the fluid on OCT 11 so the author only included patients in this study who had undergone at least eight aflibercept injections over 12 months to make sure the patient with DME was truly recalcitrant to aflibercept treatment. Recurring anti-VEGF treatments over long time periods may produce immunoreactivity and tachyphylaxis with reduced therapeutic effect, 12 and changing to another anti-VEGF medication may sometimes overcome this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Although the response to anti-VEGF therapy is reported to be good, persistent or resistant macular edema may also be seen ( 7 - 9 ). In addition, control of macular edema and retinal structure with OCT is recommended after 3 to 5 intravitreal anti-VEGF loading doses in diabetic macular edema ( 10 , 11 ). Although three loading doses are generally valid in Türkiye, there may be differences between the opinion of physicians and clinics.…”
Section: Discussionmentioning
confidence: 99%